'Primary small cell carcinoma of tonsil: An extreme rarity.'. (August 2019) - Sen, Rajeev; Bhutani, Namita; Saini, Reeti; Jashanpreet,
Abstract: Introduction: Small cell neuroendocrine carcinoma (NEC) that originates in the tonsil is extremely rare and carries a poor prognosis. Only a few cases of this tumor have been reported so far and the standard treatment protocol remains uncertain. Case report: Here, we describe a 65-year-old woman presenting with throat pain. Computed tomography (CT) scan revealed a mass with moderate enhancement in the right tonsil. A biopsy of the tonsillar mass was performed and histologic examination revealed small round to oval tumor cells arranged in cords or nests, containing hyperchromatic nuclei and scant cytoplasm. Mitotic figures were readily identified. Immunohistochemical staining further corroborated the diagnosis. A diagnosis of primary small cell NEC of the left tonsil was rendered. The patient was treated by six cycles of cisplatin combined with etoposide and the masses showed initial complete response. We also provide a succinct review of all tonsillar SCC cases reported in the English literature and their outcomes. Conclusion: Small Cell Carcinoma of the tonsil is an extremely rare entity with an aggressive disease course and poor prognosis. Therefore, it is important for the clinicians to be aware of the uncommon occurrence of this disease and its management. Highlights: Small cell NECs of the tonsil are extremely rare and only a few cases were added since it was firstly repoted. The cell of origin was initially thought to be from amine-precursor uptake and decarboxylase (APUD or Kulchitsky) cells; however, the current opinion favors their origin from multipotential stem cells. Thus far, the therapeutic strategy has not been properly formulated due to the paucity of data.